Retinopathy of Prematurity and Neurodevelopmental and Quality-of-Life Outcomes at 10 Years of Age - Sriram, Sudhir; Jensen, Elizabeth T.; Msall, Michael E.; Yi, Joe X.; Zhabotynski, Vasyl; Joseph, Robert M.; Kuban, Karl C.K.; Frazier, Jean A.; Hooper, Stephen R.; Santos, Hudson P., Jr.; Gogcu, Semsa; Dammann, Christiane; Dammann, Olaf; Shenberger, Jeffrey; Fry, Rebecca C.; O'Shea, Thomas Michael; for the ELGAN-ECHO Study Investigators (American Journal of Perinatology, 2025)
To evaluate, in a cohort of children born extremely preterm, the hypothesis that increasing severity of retinopathy of prematurity (ROP) is associated with less optimal vision, neurodevelopmental outcomes, and parent-reported quality of life.The Extremely Low Gestational Age Newborn study is a multicenter, longitudinal cohort study. Study participants were born before 28 completed weeks of gestation during the years 2002 to 2004 and were enrolled at birth at 14 U.S. hospitals. Based on retinal examinations by ophthalmologists, participants were classified during their initial hospitalization according to the severity of ROP. At 10 years of age, study psychologists evaluated participants' cognitive abilities, academic achievement, and behaviors indicative of autism spectrum disorder. Participants were classified with regard to gross motor function, anxiety, depression, and quality of life based on parents' responses on standardized questionnaires.After adjustment for confounders, increased severity of ROP was associated with increased severity of vision/eye problems, worse scores on math achievement tests, as well as higher prevalence of anxiety and lower quality of life as reported by the parent when the child was 10 years old. A history of blindness in one or both eyes was associated with these same outcomes, as well as worse scores on assessments of cognitive function, reading ability, and social responsiveness.Among extremely preterm children, severe ROP and severe eye or vision problems are associated with adverse neurodevelopmental outcomes and lower quality of life.
Keywords: extremely low gestational age neonates; cognitive function; quality of life; retinopathy of prematurity